Electrocatalytic Oxidation of Carbohydrates via Surface-Immobilized Viologen. Issue 10 (20th October 2021) - Paxton, Walter F.; Humphries, Preston A.; Scott, Dallin D. V.; Han, Haesook; Bhowmik, Pradip K.
Abstract : Electricity produced directly from renewable carbohydrates—Earth's most abundant biomolecules—offers tremendous potential if it can be done cheaply, efficiently, and practically. Previous work demonstrated that the viologen-mediated process accelerates carbohydrate oxidation but also results in incomplete oxidation products reducing the efficiency of electricity production. Subsequent studies suggested that soluble polymeric viologen compounds improved oxidation efficiency by increasing the local concentration of the viologen mediators. In the present study, the utility of surface-immobilized viologen mediators for the oxidation of simple carbohydrates was investigated. Self-assembled monolayers of thiolated viologen derivatives were prepared on gold anodes to enhance the electrocatalytic oxidation of dihydroxyacetone, fructose, and glucose. The thiolated viologen mediators formed surface-adsorbed films on gold electrodes that were consistent with incomplete monolayers, as characterized by quartz crystal microbalance and cyclic voltammetry. Monolayers formed from dialkylated viologens enhanced the spontaneous electrooxidation of carbohydrates in an unoptimized alkaline electrochemical cell. These results indicate that immobilized mediators can be used to enhance the spontaneous oxidation of carbohydrates to generate electricity from renewable sources. The same tethered-mediator strategy could be used for other mediators to increase the electrochemical cell efficiency and enable long-lasting anodes in carbohydrate fuel cells.